2008
DOI: 10.1177/0163278708315926
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Adaptation Process for International Dissemination of the Strengthening Families Program

Abstract: The Strengthening Families Program (SFP) is an evidence-based family skills training intervention developed and found efficacious for substance abuse prevention by U.S researchers in the 1980s. In the 1990s, a cultural adaptation process was developed to transport SFP for effectiveness trials with diverse populations (African, Hispanic, Asian, Pacific Islander, and Native American). Since 2003, SFP has been culturally adapted for use in 17 countries. This article reviews the SFP theory and research and a recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
204
1
18

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(226 citation statements)
references
References 36 publications
3
204
1
18
Order By: Relevance
“…The outcomes of the implementations carried out in the Spanish adaptation, in their implementation in primary care social services, are as consistent as the ones offered by the SFP in benchmark implementations and in international adaptations (Kumpfer and Alvarado, 2003;Kumpfer, et al 2008), showing their effectiveness along the same lines as these studies.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The outcomes of the implementations carried out in the Spanish adaptation, in their implementation in primary care social services, are as consistent as the ones offered by the SFP in benchmark implementations and in international adaptations (Kumpfer and Alvarado, 2003;Kumpfer, et al 2008), showing their effectiveness along the same lines as these studies.…”
Section: Discussionsupporting
confidence: 65%
“…Los resultados de las aplicaciones realizadas en la adaptación española, en su aplicación en los servicios sociales de atención primaria, son tan consistentes como los ofrecidos por los del SFP en las aplicaciones de referencia y en las adaptaciones internacionales (Kumpfer y Alvarado, 2003;Kumpfer, et al 2008), mostrando su eficacia de acuerdo a dichos estudios.…”
Section: Discussionunclassified
“…There is a consensus among the different models and frameworks for cross-cultural and crosscontext adaptation that it is critical to maintain fidelity to the essential-or causally effective-components of the intervention so that it preserves its effectiveness in the new setting. 7,[16][17][18][19] To do so, however, requires these components be empirically identified through methods such as decomposing trials, mediational analyses and micro-trials. 20 The extent to which the 18 model elements specified by the NFP are causally effective and how faithfully they each have to be implemented before the intervention begins to lose its effectiveness remain unclear.…”
mentioning
confidence: 99%
“…Rather, it seems-when applying innovative statistical methodologies (Brown et al 2011;Muthén et al 2002)-that universal prevention can be more beneficial for the more vulnerable subgroups. Recent evaluations of universal prevention programs have shown such effects on the more vulnerable children in elementary school (Kellam et al 2008); some selective family based programs seem to be more effective the more vulnerable the targeted families are (Kumpfer et al 2008); a school-based program, evaluated in seven European countries under the EU-DAP trial, showed a more favorable effect on problematic drinking among students in underprivileged social environments (Caria et al 2011); and the evaluation of an alcohol prevention program in both school and family settings combined (Koning et al 2012) found that the more vulnerable subgroups within the universal target population benefited more from the intervention. This might be due to vulnerable subgroups adjusting their behavior to that of the "conventional" majority.…”
mentioning
confidence: 99%